Pengembangan dan pengujian inokulum untuk pengomposan limbah tandan kosong kelapa sawit - Suharwaji Sentana; Suyanto Suyanto; M. A. Subroto; Suprapedi Suprapedi; Sudiyana Sudiyana (Jurnal Rekayasa Proses, 2010)
Empty palm oil bunch waste is about 23% of the fresh bunches which is rich with important macro and micro nutrients for plant growth. However, those have not been optimally utilized. The objective of this experiment was to develop and to evaluate the inoculums which could be used to make compost from empty palm oil bunch wastes. The inoculums consisted of fungies and bacteria isolated from the empty palm oil bunches. The isolates were then grown and fermented on to a particular media. The inoculums were then evaluated at laboratory scale according to the following methods. About 2 kg of 2 cm long crushed empty palm oil bunches were put in particular places and were then inoculated by the inoculums at a dosage of 500 and 1000 ml/ton of wastes. The experiment was done at triplicates and the relative humidity during the experiment was kept constant at 60%, and temperature was recorded until the end of the experiment. Water, carbon, nitrogen, phosphor, potassium, and magnesium contents of the composts were analysed. The inoculums that consisted of fungies and bacteria were successfully developed and it was called “Indigenous Microbial Consortium”. The inoculums could be used to make good quality of composts.